Black Religion and Black Power: The Nation of Islam’s Internationalism - Bayyinah S. Jeffries (Genealogy, 2019)
The Nation of Islam’s influence has extended beyond the United States. This Black American Muslim movement has used the intersection of race and religion to construct a blueprint of liberation that has bonded people of African descent throughout the Diaspora. Their transnational dimensions and ideas of freedom, justice and equality have worked to challenge global white imperialism and white supremacy throughout the 20th century and beyond.